User's guide to correlation coefficients - AKOĞLU, HALDUN (ELSEVIER SCIENCE BV, 2018)
When writing a manuscript, we often use words such as perfect, strong, good or weak to name the strength of the relationship between variables. However, it is unclear where a good relationship turns into a strong one. The same strength of r is named differently by several researchers. Therefore, there is an absolute necessity to explicitly report the strength and direction of r while reporting correlation coefficients in manuscripts. This article aims to familiarize medical readers with several different correlation coefficients reported in medical manuscripts, clarify confounding aspects and summarize the naming practices for the strength of correlation coefficients.
Keywords: Correlation coefficient; Interpretation; Pearson's; Spearman's; Lin's; Cramer's